Fragmentation Analysis of Plasma DNA Reveals Its Prognostic Value in Gastric Cancer - Ebru Esin Yoruker,; Emre Ozgur,; Metin Keskin,; Ilker Ozgur,; Ugur Gezer, (Turkish Journal of Gastroenterology, 2021)
Background: Gastric cancer (GC) is a common cause of cancer-related deaths. The poor clinical outcome in GC patients is partially associated with a lack of appropriate diagnostic and prognostic biomarkers. In the present study, we evaluated the diagnostic and prognostic values of cell-free DNA (cfDNA) integrity and the concentration of circulating nucleosomes (cNUCs). Methods: In the study, 40 GC patients and 55 GC-free individuals were enrolled. Cell-free DNA integrity was calculated as the ratio of concentration of the longer ACTB (beta-actin) gene fragment to that of the shorter ACTB fragment, measured using quantitative PCR. Circulating nucleosomes were measured by an ELISA-based approach. Results: We found that cfDNA integrity is higher in GC patients than in the control subjects (relative median values 0.51 vs. 0.38, respectively, P = .56) indicating prominent abundance of longer fragments in the patients. The patients with larger tumors (T3-4) had significantly higher cfDNA integrity than those with T1-T2 tumors. We also found GC patients to have higher concentrations of cNUCs in their plasma (relative median values 3.64 vs. 3.1). Importantly, the patients with high cfDNA integrity (i.e., lower fragmentation) had longer overall survival rates at 3 years than those with lower cfDNA integrity (76.5% vs. 38.9%, P = .02). Conclusion: Cell-free DNA fragmentation has a prognostic value. However, it has no diagnostic value in GC. Cite this article as: Esin Yoruker E, Ozgur E, Keskin M, Ozgur I, Gezer U. Fragmentation analysis of plasma DNA reveals its prognostic value in gastric cancer. Turk J Gastroenterol. 2021; 32(9): 720-726.